(untitled) (Research, Society and Development, 2020)
The aim of this work was to evaluate the lipolytic capacity of yeasts isolated from different Tocantinense Savana´s palm fruits in solid medium supplemented with Tween 20 at 25, 35 and 40º C evaluating the enzymatic index (EI). It was evaluated the effects of pH, temperature, agitation, (NH4)2SO4 and yeast extract concentration in submerged culture to two strains with the highest EI, using a Plackett-Burman (PB) design, for this, an exploratory, laboratory study of a quantitative nature was carried out. From the 150 strains tested 24 (16%) showed positive results at 25 ºC, 12 (8%) at 35 ºC and none of the strains presented activity at 40 ºC. The highest EI values obtained were 6.0 and 5.0 at 25 ºC by T194 and T199, respectively. The PB results showed that just the (NH4)2SO4 had significant influence in lipase production whose values ranged from 34.3 U.mL-1 (T194) to 43.6 U.mL-1 (T199). A completely randomized design with different levels of (NH4)2SO4 was conducted and there was no significant effect to T194 strain, but concentration among 30 and 35 g.L-1 showed significant effect to T199 strain, and the lipase activity ranged from 61 to 70.1 U.mL-1. The medium supplemented with (NH4)2SO4 increased the lipase production from 34.3 to 60 U.mL-1 to T194 strain and from 43.6 to 70.1 U.mL-1 to T199 strain.